Anal Dysplasia in Human Immunodeficiency Virus-Infected Men Who Have Sex With Men With Sexually Acquired Early Hepatitis C Virus Infection. (25th November 2019) - Jacobson, Karen B; Gaisa, Michael M; Sigel, Keith; Foster, Andrew L; Fierer, Daniel S; ,
Abstract: Background: Human immunodeficiency virus (HIV)-infected men who have sex with men (MSM) are at increased risk of anorectal infection with high-risk human papillomavirus and subsequent high-grade squamous intraepithelial lesions (HSIL), the putative precursor to anal cancer. Recently, an epidemic of sexually transmitted hepatitis C virus (HCV) has emerged that shares this anorectal route of transmission. We hypothesized that the prevalence of anal HSIL would be high in HIV-infected MSM with sexually acquired early HCV infection. Methods: High-resolution anoscopy (HRA) findings from a cohort of HIV-infected MSM with sexually acquired early HCV infection were compared with HRA findings from a contemporary cohort of HIV-infected MSM without HCV infection who underwent HRA due to abnormal anal cytology found during routine screening. Results: Sixty HIV-infected MSM with sexually acquired early HCV infection and the comparator group of 1150 HIV-infected MSM with abnormal anal cytology but without HCV underwent HRA. The HIV-infected MSM with sexually acquired early HCV had higher CD4 counts compared with the comparator group (656 and 541 cells/μL, respectively; P = .02). Despite this, the prevalence of anal dysplasia was as high among MSM with early HCV as in the comparator group of MSM with abnormal cytology (47 [78%] and 941 [82%], respectively; P = .50), as was the proportion with HSIL (25 [42%] and 379 [33%], respectively; P = .17). Conclusions: The prevalence of anal dysplasia in HIV-infected MSM with sexually acquired early HCV infection was as high as that of HIV-infected MSM with abnormal anal cytology. These findings suggest that primary screening with HRA may be warranted for HIV-infected MSM with early HCV.